P241. (21st January 2022) - Cifù, A; Marino, M; Sablich, R; Carletti, M; Blasone, N; Milloch, S; Curcio, F; Fabris, M
Abstract: Background: In recent decades, biological drugs targeting anti-tumour necrosis factor-α (TNF-α) have represented the cornerstone in the treatment of inflammatory bowel diseases. Currently, anti- TNF-α represents a breakthrough in patient care. However, 20–50% of patients experience primary or secondary loss of response. This may be due to pharmacodynamic and/or pharmacokinetic issues, resulting in subtherapeutic drug concentrations, frequently related to the development of anti-drug antibodies (ADA). In this context, therapeutic drug monitoring (TDM) is essential to patients' management in order to pinpoint the basis of reduced efficacy. Indeed, a fast and reliable assessments of TDM is mandatory to allow rapid intervention, to avoid toxicity and improve treatment efficacy. In this study we assess the analytical performance of a novel fully automated chemiluminescent assay in measuring biological drugs levels and ADA serum concentration and to compare its performances to the current diagnostic method (ELISA). Methods: Serum levels of biological drugs (Infliximab and Adalimumab) and their respective ADA were measured in twenty infliximab (IFX)-treated IBD patients and twenty adalimumab (ADL)-treated IBD patients using both the Promonitor® ELISA kits (Grifols) and the i-TRACKER chemiluminescent (CLIA) kits (Theradiag Results: The CLIA method is a random-access platform that allows the continuous loading of samples, while the ELISA is a time-consuming manual method to be planned in advance to reduce expenses. Actually, in our laboratory is performed only twice a month. A very good correlation was observed both for Infliximab (Spearman r=0.9695, 95%CI = 0, 92-0, 99, p<0.0001) and Adalimumab serum levels (Spearman r=0.9476, 95%CI = 0, 86-0, 98, p<0.0001). Among the patients with undetectable IFX serum levels, 6/8 (75%) resulted ADA positive by ELISA versus 8/8 (100%) by CLIA. Moreover, CLIA disclosed very high ADA concentration in 3 samples compared to borderline results by ELISA. Regarding ADL, all the 9 patients with undetectable serum levels presented similar ADA concentration as tested with ELISA or CLIA. Conclusion: In conclusion, the i-TRACKER CLIA Infliximab and Adalimumab assays showed a very good correlation for serum-based drugs level quantification as compared to the related ELISA methods. Furthermore, a good agreement was observed for ADA analysis, with a higher sensitivity against anti-IFX antibodies by CLIA compared to ELISA. Our data clearly highlighted that a fully automated assay for TDM would certainly reduce costs and significantly improve the management of IBD patients in terms of a shorter turn-around time.